Elimination of hospital‐acquired central line–associated bloodstream infection on a mixed‐service pediatric unit. Issue 3 (23rd June 2021) - Mezoff, Ethan A.; Roberts, Erika; Ernst, Daniel; Gniadek, Michelle; Beauseau, Wendi; Balint, Jane; Ardura, Monica I.; Dienhart, Molly
Abstract: Introduction: Hospital‐acquired central line‐associated bloodstream infections (CLABSI) are "never events" in U.S. healthcare. National efforts to improve CLABSI rates are ongoing. Efforts are important for all patients with a central venous catheter (CVC) and critical to children with intestinal failure (IF) who depend on long‐term, daily use of a CVC and undergo extended hospitalizations. We describe outcomes of a multidisciplinary CLABSI elimination effort on a 24‐bed medical‐surgical unit caring for children with IF. Methods: Unit CLABSI events from 1/9/2012 to 4/16/2020 were evaluated with multiple improvement interventions. We leveraged prospectively maintained clinical registries and National Healthcare Safety Network (NHSN) reporting data to extract patient and unit demographics, ethanol lock utilization, and unit CVC days. Interventions were developed utilizing expert consensus and CDC guidelines with active frontline staff engagement. Descriptive statistics and tests of non‐parametric data were employed for analysis. Results: Ninety‐five patients with IF and 862 non‐IF patients experienced a total of 1, 629 admissions with 20, 372 CVC days. Twelve hospital‐acquired CLABSI events occurred during the study period, including 7 following NHSN definition change on 1/1/2015 (0.56 per 1, 000 CVC days). After the last unit CLABSI on 12/5/2016, there were 7, 117 CVC days through study conclusion. Conclusions: Described interventions with an enhanced culture of collaborative care profoundly improved hospital‐acquired CLABSI occurrence. Success in a specific population translated to all other unit patients with a CVC. Findings suggest elimination is not the result of a single new product or practice, but also includes support and empowerment of those caring for the patient and their CVC.